Resources books for teachers : - Wajnryb, Ruth (Oxford Univ. Press, 1999)
Each book in this series provides the classroom teacher with a guide to the practice of key aspects of language teaching, and considers some of the underlying concepts. Introductions presenting important current issues in key areas of language learning are followed by examples and discussions of actual classroom materials and techniques. Designed to help English language students improve their understanding and use of grammar, this work provides an opportunity for learners to use productive grammar in the task of text creation.